ASEAN Amid Mekong's Overlap Institutions: Visible or Invisible? - Permata, Inda Mustika (Departemen Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Padjadjaran, 2023)
The Mekong region is strategic in terms of economics and geopolitics. Besides being home to mainland Southeast Asia countries, external state actors play around in the region, such as the United States, Japan, Korea, and India. They established institutions as a cooperation framework to maximize the region's potential. Over time, ASEAN remains the central organization for cooperation in East Asia, but the numerous cooperations in the Mekong will have implications for ASEAN. This article aims to provide an overview of the dynamics of overlap institutions in the Mekong Region, focusing on ASEAN's position in these cooperative efforts. The overlap institution is used as a conceptual framework. This article applies a qualitative method with secondary data. The Mekong region has multi-membership because the interests of the major actors and countries are intertwined. Therefore, they are trying to open up new opportunities by forming other institutions. In addition, the dynamic will shake East Asia's regional integration.